Correction to: Digital technologies for Early Modern Portuguese manuscripts: an experiment with two 'Handwritten Text Recognition' software applications. (Digital Scholarship in the Humanities, 2026)
This correction notice addresses an error in the spelling of author Maria Clara Ramos Morales Crespo’s name in a previously published article on the use of digital technologies for Early Modern Portuguese manuscripts, specifically involving experiments with two Handwritten Text Recognition software applications. The correction ensures the accurate representation of the author’s name in the official record. No other content or findings from the original article are affected.